Does Acupuncture Have Any Benefit in the IVF Treatment of Couples with Unexplained Infertility; A Prospective Randomized Controlled Trial - Songul Ece Gonen; Pınar Kadirogullari; Kerem Doga Seckin; Bunyamin Borekci (Medical Network, 2020)
Objective: We aimed to investigate the effect of acupuncture performed as an adjuvant therapy to in vitro fertilization, on pregnancy rates by performing acupuncture on the day of embryo transfer, one hour before the procedure and one hour after the procedure. Study Design: In this open-label randomized prospective controlled study, 60 unexplained infertility patients enrolled for in vitro fertilization treatment were randomized by a computer-based number generator for acupuncture performance and no-treatment. All patients received rFSH (Gonal-F®) for ovulation induction and the antagonist Cetrorelix (Cetrotide®) to prevent premature ovulation. Ovulation was triggered by using hCG (Ovitrelle®) and egg collection was done after 36-48 hours. In the study group, acupuncture was performed by intradermal needling, bilaterally with a sterile needle, both one hour before and one hour after the embryo transfer. Acupuncture was not performed on the control group. The results of the treatment were evaluated 12 days after embryo transfer. Results: Thirty patients were randomized into the study group and 30 patients were randomly placed in the control group. Although there was no statistically significant difference between groups in terms of β-hCG positivity, it was 43.3% in the study group and 36.7% in the control group (p>0.05). Conclusion: The success rate of in vitro fertilization was higher in terms of pregnancy rate in the patient group who received acupuncture procedure as well, but the difference was not statistically significant. This may be due to the type of acupuncture procedure selected or insufficient sample size. As a result, further studies involving larger numbers of participants and using different acupuncture techniques are needed.